(untitled) (Praxis Educativa, 2016)
All educational technology, all pedagogy, has always explicit or implicit a philosophy of education, in order to determine the purposes of it, which will later lead to educational policies decided by the State. This article analyzes two paradigms in education: one conservative, the other progressive. Both of them hold education as a universal right, one from a “substitutionalist” universalism and the other from an “interactive” universalism. Only in the second one the differences can be thought as dismissing the hegemonic subject for which the recognition of the Other and the Other as an alter ego, mediated by narrative and dialogue is indispensable. This dialogue requires a comprehensive, understanding listening, that always reinforces the arguments of the other (he or she). This communication will be politically efficient if an inclusive moral contract exists. A contract that makes an invitation to tend bridges of listening as a precondition to collective construction.